ACTIVE LEARNING AND THE DEVELOPMENT OF CLINICAL REASONING: CONTRIBUTIONS AND LIMITATIONS IN BRAZILIAN MEDICAL SCHOOLS (REMUNOM, 2026)
The development of clinical reasoning is a central competency in contemporary medical education, requiring the integration of biomedical knowledge, clinical skills, and evidence-based decision-making. In this context, active learning methodologies have been increasingly incorporated into Brazilian medical school curricula as strategies to foster student engagement and strengthen the integration between theory and clinical practice. This study aimed to analyze, through a qualitative narrative literature review, Brazilian scientific production regarding the relationship between active learning methodologies and the development of clinical reasoning. The search was conducted in the SciELO and LILACS databases, including publications from 2015 to 2025. Findings indicate that strategies such as Problem-Based Learning, structured case discussions, simulation, and formative assessment are described as promoters of clinical thinking. However, limitations were identified, including the lack of explicit curricular intentionality, weaknesses in pedagogical training for faculty members, and inconsistencies between teaching and assessment practices. It is concluded that active methodologies hold significant potential for fostering clinical reasoning, provided they are supported by qualified faculty mediation, structured feedback, and progressive curricular organization. The consolidation of this competency requires systemic coherence among curriculum design, pedagogical practice, and assessment processes.